2021
DOI: 10.1038/s41598-021-85909-9
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Japanese pepper (Zanthoxylum piperitum De Candolle) domestication using RAD-Seq

Abstract: Japanese pepper, Zanthoxylum piperitum, is native to Japan and has four well-known lineages (Asakura, Takahara, Budou, and Arima), which are named after their production area or morphology. Restriction-site associated DNA sequencing (RAD-Seq) was used to analyse 93 accessions from various areas, including these four lineages. Single nucleotide variant analysis was used to classify the plants into eight groups: the Asakura and Arima lineages each had two groups, the Takahara and Budou lineages each had one grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Zanthoxylum (Rutaceae) is one of the most important economic and medicinal tree species in southwestern China and some regions of Asia, such as Japan, South Korea, India, Pakistan, Nepal and so on [ 23 , 24 ]. Due to the special numbing taste of its fruits, it is a very famous and essential ingredient in Sichuan hot-pot in China, and is often used to flavour some delicious dishes in many countries [ 25 , 26 ]. Zanthoxylum armatum DC., commonly named green prickly ash, is not only enriched in special numbing substances, but also has a special fragrance, and the colour of its fruit is green, all of which contribute to its increasing popularity in recent public diets [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zanthoxylum (Rutaceae) is one of the most important economic and medicinal tree species in southwestern China and some regions of Asia, such as Japan, South Korea, India, Pakistan, Nepal and so on [ 23 , 24 ]. Due to the special numbing taste of its fruits, it is a very famous and essential ingredient in Sichuan hot-pot in China, and is often used to flavour some delicious dishes in many countries [ 25 , 26 ]. Zanthoxylum armatum DC., commonly named green prickly ash, is not only enriched in special numbing substances, but also has a special fragrance, and the colour of its fruit is green, all of which contribute to its increasing popularity in recent public diets [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…armatum is planted as the second most important medicinal species in Pakistan [ 32 ]. The fruit pulp of Zanthoxylum could be extended to treat skin diseases, toothache, fever, and stomach ache [ 24 , 26 , 30 ]. Plant-based medications are a high proportion of prescription used in regions of health care scarcity [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we determined the presence or absence of asexual reproduction by setting the value of conservation at nearly 40% as the criterion. It should be noted that a similar value of conservation was also used as a criterion for clonal propagation in a study of Japanese pepper that used de novo analysis of RAD-Seq data 28 .…”
Section: Resultsmentioning
confidence: 99%
“…No reports exist on the genetic relationships and intraspecific diversity of A. macrostemon using either traditional or high-throughput methods. Encouraged by our research group's previous successes with RAD-Seq or ddRAD-Seq in analyzing various species, including loquat 26 , 27 , Japanese pepper 28 , citrus 29 31 , and firefly 32 , we are inspired to apply this knowledge to the study of A. macrostemon .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several such lineages, it was not known whether each of these lineages is genetically distinct from the others. Therefore, our research group has previously conducted a genome-level classification of cultivated and wild species of Japanese pepper in various regions of Japan using RAD-Seq (Restriction Site Associated DNA Sequencing) [ 21 ] and has found that each lineage can be identified at the DNA level. The next challenge is to analyze and identify the differences in the properties of these different lineages.…”
Section: Introductionmentioning
confidence: 99%